The war on street ‘terror’: why tackle anti-social behaviour? - Koemans, Monique (Crime, law and social change, 2010)
This article examines the rationales of Dutch politicians for tackling the perceived pressing problem of ‘anti-social behaviour’ (ASB) and the question did they copy the British approach? The first part will describe in short the concept of policy transfer and the recent British fight against ASB. The focus will be on the introduction of the Anti-social Behaviour Order. The second part is an empirical study into the Dutch retreat from ‘condoning’ ASB, consisting of interviews with Dutch politicians focusing on their ideas for tackling ASB. Those are compared with the British’s rationales. This kind of comparative elite ethnography is not common in criminology, but this article aims at providing evidence of its benefits. By answering the research question an insight into the origins of policy in the sphere of criminal justice can be obtained.